Horizons in clinical nanomedicine - Karagkiozaki, Varva; Logothetidis, Stergios (Pan Stanford, 2014)
Nanomedicine-the application of nanotechnology to health sciences-has the potential to address many important medical problems by exploiting the advanced physicochemical characteristics of nanostructured materials and devices. It can revolutionize conventional medicine by offering cutting-edge developments in the processes of diagnosing, treating, and preventing diseases, injuries, or genetic disorders. Thus, clinical nanomedicine holds promise to preserve and improve human health. This book provides a comprehensive overview on the forefront developments of nanotechnology in various domains of.